Is the ether group hydrophilic or hydrophobic? - Menger, Fredric M (Langmuir : the ACS journal of surfaces and colloids, 2005)
A series of six surfactants, each with two ether oxygens within otherwise all-hydrocarbon chains, were synthesized and examined for their colloidal properties. Since an ether oxygen is sterically and conformationally similar to the methylene group it has replaced, the ether effect on micellization should stem mainly from solvation of the oxygen and, possibly, disrupted hydrophobicity of its adjacent carbons. It was found that critical aggregation values among the surfactants differ only modestly despite the total length of the ether-separated carbon segments ranging from 12 to 18. Shorter ether surfactants with only 12 or 14 total carbons appear to form small, loose aggregates owing, presumably, to a mild hydrophilicity of the ether groups. A surfactant with 18 chain carbons has a greater tendency to associate hydrophobically, but this is counterbalanced by a relatively water-free environment encountered by the ether groups within a more conventional micelle interior. The result is a leveling effect in which the critical aggregation concentration (cac) loses it sensitivity to chain length. Above their cac's, none of the ether surfactants is a good solubilizer of tetramethysilane or mesitylene. This is not necessarily a predictable finding since it was conceivable that the presence of interior ether groups might actually enhance solubilization (much as ether is a better solvent than hexane). Foamability and solid adsorption studies also indicate that the ethers impair surface activity. In response to the question posed in the paper's title, two ether groups are not sufficiently hydrophilic to prevent aggregation, but they do manage to alter the micelles' morphology and properties considerably